Students' Critical Thinking Skills on The Topic of Environmental Change - Salmi, Amalia; Sarkity, Dios; Fernando, Adam (Jurnal Ilmiah Profesi Pendidikan, 2025)
The 21st century is marked by globalization and rapid technological development, making critical thinking an essential skill. Incorporating biology into education is seen as a way to strengthen these abilities. However, many students still struggle with thinking critically, especially regarding environmental issues. This study assessed the critical thinking skills of 10th-grade students at SMA Negeri 4 Tanjungpinang during the 2023/2024 academic year. Using a descriptive approach, researchers evaluated 31 students through essay-based tests without altering any conditions. The analysis revealed that students' critical thinking was generally weak, particularly in areas such as giving basic explanations, reasoning, drawing conclusions, and providing deeper clarification. Nonetheless, they showed stronger performance in applying strategies and tactics. These findings highlight the need for teaching methods like problem-based learning to foster better critical thinking in students.